Mechanisms of Action Contributing to Reductions in Suicide Attempts Following Brief Cognitive Behavioral Therapy for Military Personnel: A Test of the Interpersonal-Psychological Theory of Suicide. Issue 2 (3rd April 2018) - Bryan, Craig J.; Wood, David S.; May, Alexis; Peterson, Alan L.; Wertenberger, Evelyn; Rudd, M. David
Abstract : Brief cognitive behavioral therapy (BCBT) is associated with significant reductions in suicide attempts among military personnel. However, the underlying mechanisms of action contributing to reductions in suicide attempts in effective psychological treatments remain largely unknown. The present study conducted a secondary analysis of a randomized controlled trial of BCBT versus treatment as usual (TAU) to examine the mechanisms of action hypothesized by the interpersonal-psychological theory of suicide (IPT): perceived burdensomeness, thwarted belongingness, and fearlessness about death. In a sample of 152 active duty U.S. Army personnel with recent suicide ideation or attempts, there were significantly fewer suicide attempts in BCBT, but there were no differences between treatment groups from baseline to 6 months postbaseline on any of the 3 IPT constructs or their interactions. Tests of the moderated mediation failed to support an indirect effect for the IPT model, regardless of which IPT variables were specified as mediators or moderators. Results suggest that the IPT's hypothesized mechanisms of action do not account for reductions in suicide attempts in BCBT. Implications for clinical practice and research are discussed.